Pengasuhan Tumbuh Kembang Balita pada Wanita Penyandang Disabilitas di Kabupaten Semarang - Risma Aliviani Putri; Puji Lestari (Universitas Ngudi waluyo, 2018)
The stigma about the ability of disabled womenâ€™s role as a mother having problems in taking care child is often doubted by society. People think that a child who does not grow optimally is caused by the limitation of a disabled mother. The purpose of this research was to know how the care for the growth and development of under five children done by a disabled mother in Semarang regency.Â The type of this research was descriptive qualitative. The subjects of this research were called as informants consisting of 4 family informants and 3 triangulation informants. Qualitative data analysis was done interactively and continuously until the research ended. The research results showed that the four main informants gave a good care seen from the sufficient interaction quality with their children and their willing to let their children do activities as they want under their supervision. The care done by disabled women have a good effect toward the growth and the development of children under five. Therefore, the care done responsibly and the willing to let their children do activities under their supervision create an optimal growth for children under five.